Mangrove plants in coastal area of Central Java: 2. Floristic composition and vegetation structure - AHMAD DWI SETYAWAN; INDROWURYATNO INDROWURYATNO; WIRYANTO WIRYANTO; KUSUMO WINARNO; ARI SUSILOWATI (Biodiversitas Journal of Biological Diversity, 2005)
The study was intended to observe the vegetation composition and structure of mangrove plants on southern and northern coast of Central Java Province. This research was conducted in July till December 2003, at 20 sites. Laboratory assay was done in Laboratory of Biology Department, Faculty of Mathematics and Natural Sciences, and Central Laboratory of Mathematics and Natural Sciences, Sebelas Maret University (UNS) Surakarta. Data was collected by using belt transect method, from coast line into landward. The result indicated that in common, the trees strata which also have shoots strata and strata of germs (seedlings); and bushes strata which also have strata of germs(seedlings), if they were compared to the same species then their important value tend to be stable. So it was predictable that in the disturbance condition, the preservation of mangrove was guaranteed, as long as there was no great change on a broad scale.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: mangrove plants, Central Java Province, composition and vegetation structure